The Effect of Total Quality Standards on Developing Textile Arts-Based on Creativity of Najran University Students - Dr. Wafaa Mohamed Ibrahem Elbana; Dr. Shreen Hassan Mahmoud Hegazy (Journal of Arts, Literature, Humanities and Social Sciences, 2021)
There is no doubt that the interest in the quality of production started in tandem with the beginning of the human learning of the letter, and this interest has increased with time. The increase in civil and its complexities , The multiplicity of competition between individuals, companies, and countries led to precise requirements for product quality , And this accuracy continues to evolve with the development of measuring devices tremendously due to the need for the purposes to be achieved according to the desires of the consumer. The current research aims to identify the extent of opening new areas of work through textile artifacts of an aesthetic and utilitarian nature and the use of total quality in their production to obtain the highest standards of quality and consumer satisfaction. The study relies on the descriptive and analytical approach in addition to the applied study due to the nature of the research that uses the description and analysis of designs. The study relied on using the tissue composition 1/1 to produce textile artifacts of an aesthetic nature and have multiple utility uses provided that this is done within the framework of comprehensive quality standards to achieve the highest possible Of the specifications that distinguish the product and satisfy the consumer. The study sample consists of a group of female students at Najran University (12 female students), and the study tools include a measure of professional skills (prepared by the researchers), textile products produced according to comprehensive quality standards (prepared by the researchers), and the data are processed statistically using the Statistical Package for Social Sciences program. SPSS by calculating the averages, standard deviations and correlation coefficients to identify the significance of the differences between the averages of the grade scores in the post and pre-measurement.